A modified class of ratio estimators for population mean. Issue 4 (16th February 2016) - Etuk, Sylvanus Itoro; Enang, Ekaette Inyang; Ekpenyong, Emmanuel John
ABSTRACT: A modified class of ratio estimators for population mean of the study variable (ϒ) under the simple random sampling without replacement scheme is proposed using a combination of scalars and known population mean of the auxiliary variable ( X ). The expressions for the bias and mean square error (MSE) were obtained and the condition for the asymptotic optimum estimator (AOE) with its bias and mean square error expressions were also obtained. Analytical and numerical comparisons of the AOE with other existing members of the proposed class of estimators show that the AOE is more efficient under certain realistic conditions.